Differing Connectivity of Exner’s Area for Numbers and Letters - Klein, Elise; Willmes, Klaus; Jung, Stefanie; Huber, Stefan; Braga, Lucia W.; Moeller, Korbinian (Frontiers in Human Neuroscience, 2016)
There is a growing body of evidence indicating a crucial role of Exner’s area in (hand-) writing symbolic codes such as letters and words. However, a recent study reported a patient with a lesion affecting Broca’s and Exner’s area, who suffered from severe peripheral agraphia for letters but not for Arabic digits. The authors suggested a speculative account postulating differential connectivity of Exner’s area for numbers and letters in order to explain this dissociation. In the present study, we evaluated this account, employing atlas-based tractography for the patient’s anatomy, deterministic fiber-tracking as well as an automated toolkit to investigate the connectivity of Exner’s area in healthy adults. In particular, fiber pathways connecting Exner’s area with areas associated with language processing (e.g., the arcuate fascicle, ventral pathways encompassing the external/extreme capsule system) reached the inferior part of Exner’s area, while fronto-parietal fibers (e.g., the superior longitudinal fascicle) connected the upper part of Exner’s area with the intraparietal sulcus typically involved in number processing. Our results substantiated the differential connectivity account for Exner’s area by identifying the neural connections between fiber tracts and cortex areas of interest. Our data strongly suggest that white matter connectivity should be taken into account when investigating the neural underpinnings of impaired and intact human cognition.